Rola najstarszych zasad pisowni (odrębnych traktatów ortograficznych i części gramatyk) oraz elementarzy w rozwoju języków słowiańskich - Tadeusz Lewaszkiewicz (Język. Religia. Tożsamość, 2023)
Spelling treatises, spelling rules in grammars, and reading primers played a major role in the development of most Slavic languages. On occasion, the primers were also the main source of knowledge on the basics of mathematics, geography, natural science, history etc. Of particular essence in language policy were those spelling treatises and primers that furthered Slavic spelling reforms.